2014
DOI: 10.5624/isd.2014.44.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alveolar ridge preservation methods using three-dimensional micro-computed tomographic analysis and two-dimensional histometric evaluation

Abstract: PurposeThis study evaluated the efficacy of alveolar ridge preservation methods with and without primary wound closure and the relationship between histometric and micro-computed tomographic (CT) data.Materials and MethodsPorcine hydroxyapatite with polytetrafluoroethylene membrane was implanted into a canine extraction socket. The density of the total mineralized tissue, remaining hydroxyapatite, and new bone was analyzed by histometry and micro-CT. The statistical association between these methods was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…All types of bone material in place of the autogenous bone are currently employed in ARP, that is, allogeneic and xenogeneic bone‐derived materials or, moreover, synthetic and alloplastic derived materials . The data seemed to attest that none of the substitutes had prevailed over the others, except for results reported in a recent meta‐analysis in which the use of a xenograft or an allograft had a beneficial effect in buccal alveolar bone height preservation, when compared to alloplastic materials …”
Section: Introductionmentioning
confidence: 99%
“…All types of bone material in place of the autogenous bone are currently employed in ARP, that is, allogeneic and xenogeneic bone‐derived materials or, moreover, synthetic and alloplastic derived materials . The data seemed to attest that none of the substitutes had prevailed over the others, except for results reported in a recent meta‐analysis in which the use of a xenograft or an allograft had a beneficial effect in buccal alveolar bone height preservation, when compared to alloplastic materials …”
Section: Introductionmentioning
confidence: 99%
“…In addition, to build a scientific basis for selection of the most suitable grafting materials for the revolution of peri‐implantitis, measurements applied are of great significance for clinicians’ awareness of newly formed local bone volume as well as re‐osseointegration situation. Thus, histologic analysis of dynamic mineralization activity and undecalcified section as well as clinic and radiographic tests are mandatory for understanding the healing response with respect to the implant‐tissue engineered bone interface …”
Section: Introductionmentioning
confidence: 99%
“…One of the latest alternatives is microcomputed tomography (micro‐CT), which has recently been introduced to characterize three‐dimensional structures in bone tissue and applied to bone research. In some articles, the comparison of histometry and micro‐CT analysis was investigated . Vinci and colleagues reported that the application of both histologic and micro‐CT techniques allows a better evaluation of grafted bone by concurrently allowing two‐ and three‐dimensional visual and morphometric analysis of bone vitality, structure, turnover, and strength…”
Section: Introductionmentioning
confidence: 99%